The skeletal phenotype of chondroadherin deficient mice. - Lovisa Hessle (Public Library of Science (PLoS), 2014)
Chondroadherin, a leucine rich repeat extracellular matrix protein with functions in cell to matrix interactions, binds cells via their α2β1 integrin as well as via cell surface proteoglycans, providing for different sets of signals to the cell. Additionally, the protein acts as an anchor to the matrix by binding tightly to collagens type I and II as well as type VI. We generated mice with inactivated chondroadherin gene to provide integrated studies of the role of the protein. The null mice presented distinct phenotypes with affected cartilage as well as bone. At 3-6 weeks of age the epiphyseal growth plate was widened most pronounced in the proliferative zone. The proteome of the femoral head articular cartilage at 4 months of age showed some distinct differences, with increased deposition of cartilage intermediate layer protein 1 and fibronectin in the chondroadherin deficient mice, more pronounced in the female. Other proteins show decreased levels in the deficient mice, particularly pronounced for matrilin-1, thrombospondin-1 and notably the members of the α1-antitrypsin family of proteinase inhibitors as well as for a member of the bone morphogenetic protein growth factor family. Thus, cartilage homeostasis is distinctly altered. The bone phenotype was expressed in several ways. The number of bone sialoprotein mRNA expressing cells in the proximal tibial metaphysic was decreased and the osteoid surface was increased possibly indicating a change in mineral metabolism. Micro-CT revealed lower cortical thickness and increased structure model index, i.e. the amount of plates and rods composing the bone trabeculas. The structural changes were paralleled by loss of function, where the null mice showed lower femoral neck failure load and tibial strength during mechanical testing at 4 months of age. The skeletal phenotype points at a role for chondroadherin in both bone and cartilage homeostasis, however, without leading to altered longitudinal growth.